THE INFLUENCE OF TOTAL POPULATION, DOMESTIC DIRECT INVESTMENT, AND GROSS REGIONAL DOMESTIC PRODUCT ON POVERTY LEVEL IN DISTRICTS / CITIES OF WEST KALIMANTAN PROVINCE PERIOD 2011 - 2016 - B1011141048, Rhut Sahana Sihombing (Jurnal Pembangunan dan Pemerataan, 2018)
Poverty is seen as an economic inability to fulfill basic needs, one of the causes is lack of income and assets.This study aimed to analyze the influence of total population, domestic direct invesment, and gross regional domestic product on poverty level in districts and cities of West Kalimantan Province.This research is an associative research that use a quantitative approach. The analytical method in this study is multiple linear regression that use the Random Effect model with Pooled EGLS method. The result show that total population and domestic direct invesment have positive effect and not significantly toward poverty level. Gross Regional Domestic Product has negative effect and significantly affect poverty level. Based on F value, total population, domestic investment, and GRDP influence significantly on the poverty level simultaneously.Keywords        : total population, domestic direct invesment, GRDP, poverty level.